Discussing the knowledge gap of coach-athlete relationships within strength and conditioning - Foulds, S. F.; Hoffmann, S. M.; Hinck, K.; Carson, F. (Journal of Australian Strength and Conditioning, 2019)
The better the strength and conditioning coach understands the constructs of the coach-athlete relationship, as well as how their behaviours are perceived by athletes, the greater the potential for enhanced athlete satisfaction and subsequent athletic performance success.